NEW DEBATES BROUGHT ABOUT BY CYBERSPACE IN HUMAN RIGHTS - AKYEŞİLMEN, Nezir (Cyberpolitik Journal, 2019)
Cyberspace, which has begun to affect every aspect of our lives, has deeply affected citizenstate relations and has brought new opportunities and threats in the field of human rights. In current international human rights law, the state is the only actor for violation of human rights and again the only actor responsible for protecting human rights. But with globalization process, non-state actors played an active role in international relations, and this traditional state-centered human rights mechanism was questioned. Today, along with cyberspace, borders and distances have been eliminated, anonymity has increased and the scale has become insignificant with the empowerment of individuals who now have the capacity to cause enormous harm to other individuals, companies and even states. Holding the state the only actor responsible for the violation and protection of human rights in multi-stakeholder cyberspace will greatly undermine and harm human rights. In short, the actor, dynamics and mechanisms of the traditional international system have been inadequate in the cyber ecosystem. Cyberspace affects human rights both positively and negatively. In addition, it has brought new debates on human rights. Some of them are whether access to the internet is a human right, the question need for a cyber human rights law, the responsibility of non-state actors for human rights, the redefinition of privacy, the right to be forgotten, the question of the physical hacking of human brain and the question on whether internet rights are a new group of rights otr not? As technology evolves, it will be inevitable that we will encounter new debates and new problems in the field of human rights. Now, the task of experts is to find solutions to these new problems within the framework of human rights paradigm.